Simultaneous double primary malignant tumors of MSS/pMMR ascending colon cancer and MSI-H/dMMR duodenal cancer with nearly 2 years of recurrence-free survival after MDT-guided comprehensive treatment: a case report - Wang, Weimin; Yang, Quan; He, Yifan; Cha, Xuefeng; Xiong, Chaoxian; Li, Xiaoxia; Li, Jie; Gao, Pin; Yu, Kun (Frontiers in Oncology, 2025)
The exceedingly rare clinical presentation of synchronous ascending colon carcinoma with duodenal adenocarcinoma demonstrating discordant mismatch repair protein expression patterns forms the cornerstone of this investigation. Through detailed analysis of a unique case featuring co-occurring MSS/pMMR ascending colon adenocarcinoma and MSI-H/dMMR duodenal adenocarcinoma, this study demonstrates the successful implementation of multidisciplinary therapeutic protocols achieving 22-month progression-free survival post-radical resection. These clinical findings offer empirical evidence for optimizing clinical management while systematically addressing diagnostic complexities and treatment dilemmas inherent to synchronous dual primary intestinal carcinomas. Particular emphasis is placed on reconciling therapeutic conflicts arising from differential tumor biology and developing precision strategies for molecularly heterogeneous synchronous malignancies.